Penerapan Metode Waterfall Untuk Perancangan Sistem Informasi Pengolahan Nilai Pada SD Nature Islam - Badrul, Mohammad; sari, Novita (STIKOM Tunas Bangsa Pematangsiantar, 2021)
SD Nature Islam is one of the educational institutions located in the Tangerang Banten area. Its activities are certainly inseparable from the activities of the teaching and learning process. The results of these teaching and learning activities are in the form of grades that are reported in a student learning progress report book or report card every semester. Nature Islam Elementary School uses the 2013 curriculum which is of course based on the Basic Competencies formulated in the curriculum. Thus, it requires teachers and staff to develop perfect assessment techniques. The use of computers is very useful and helps work become better, faster, and more efficient. The use of computers in particular will be very beneficial. in processing report cards at SD Nature Islam. However, in terms of processing report cards, they still use pen counts and calculators. This will take time and teacher labor in the process. For that we need a system that can play an important role to help the field in question run well. Good value data processing will produce report cards as a good evaluation result. To get results from processing good grades data, one of them is by utilizing existing and currently developing technology or in other words making a computerized student value data processing system using one of the methods to develop information systems, namely the waterfall method, in the form of applications web based.